2009
DOI: 10.1007/s12034-009-0058-0
|View full text |Cite
|
Sign up to set email alerts
|

Application of new tool material for electrical discharge machining (EDM)

Abstract: In EDM, Cu and graphite are commonly used as tool materials. The poor wear resistance is the drawback of these tools. In the current study, an attempt has been made to develop a ZrB 2 -Cu composite as an EDM tool material to overcome this problem. Initially, the ZrB 2 powder is prepared by self-propagating high-temperature synthesis (SHS) technique and synthesized powder is mixed with different amounts of Cu powder. Dense composite is developed by a pressureless sintering at 1250°C. The composites are tested a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 9 publications
0
10
0
1
Order By: Relevance
“…They claimed that high sintering pressure responsible for the higher material removal while lower pressure leads to easily drop-out of the Cu and Cr particles from the electrode material due to their weak bonding strength. The performance of the ZrB 2 /Cu composites as an EDM electrode has been reported by Khanra et al [48,49]. They identified that composite tool with 40% of Cooper electrode gives higher material removal and lower tool wear as compared to the Copper electrode with some loss in the surface quality as shown in the Fig.…”
Section: A Research In Composites Tool Materialsmentioning
confidence: 65%
“…They claimed that high sintering pressure responsible for the higher material removal while lower pressure leads to easily drop-out of the Cu and Cr particles from the electrode material due to their weak bonding strength. The performance of the ZrB 2 /Cu composites as an EDM electrode has been reported by Khanra et al [48,49]. They identified that composite tool with 40% of Cooper electrode gives higher material removal and lower tool wear as compared to the Copper electrode with some loss in the surface quality as shown in the Fig.…”
Section: A Research In Composites Tool Materialsmentioning
confidence: 65%
“…As mentioned earlier, the peak current is similar to the effect of the pulse-on time to the MRR. Since an increase in the peak current gives a rise to the single spark intensity, the more the heat energy transmitted into the workpiece, the more the material melted and vaporized from workpiece [24]. As shown in Figure 7(a), the MRR in EDM oil mixed with Al is higher than that in EDM oil.…”
Section: Differences In Machining Performancesmentioning
confidence: 97%
“…Si 3 N 4 dopant boosted the sinterability via the formation of interfacial ZrC phase between the particles. Khanra [16] directly tried to develop the ZrB 2 -40 wt.% Cu composite by pressureless sintering at 1250 • C for EDM study. The composite shows more metal removal rate with lesser tool removal rate than conventional Cu tool.…”
Section: Introductionmentioning
confidence: 99%